2009
DOI: 10.1016/j.eeh.2009.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Market Integration in the Golden Periphery. The Lisbon/London Exchange, 1854–1891

Abstract: The existence of a self-regulating arbitrage mechanism under the gold standard has been traditionally considered as one of its main advantages, and attracted a corresponding research interest. This research is arguably relevant not only to test for the efficiency of the "gold points", but also to study the evolution of financial integration during the so-called first era of globalization. Our first aim with this paper is to contribute to the enlargement of the scope of the literature by considering the case of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“… Esteves, Reis and Ferramosca, in ‘Market integration’, put the gold export point at 52.5 pence for a parity rate of 53.33 pence to the mil reis , during 1861–82, and 52.82 during 1882–91. The Portuguese currency unit was the real (plural reis ), of which 1 million = 1 conto .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“… Esteves, Reis and Ferramosca, in ‘Market integration’, put the gold export point at 52.5 pence for a parity rate of 53.33 pence to the mil reis , during 1861–82, and 52.82 during 1882–91. The Portuguese currency unit was the real (plural reis ), of which 1 million = 1 conto .…”
mentioning
confidence: 99%
“… See Esteves, Reis, and Ferramosca, ‘Market integration’, the only study that provides details on gold points in Portugal. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…28588) and Quinn (1996). The specie-point mechanism was first calculated for the case of the classical gold standard (Morgenstern 1959;Clark 1984;Marcuzzo and Rosselli 1987;Officer 1983Officer , 1986Officer , 1989Officer , 1996Canjels, Prakesh-Canjels, and Taylor, 2004;Esteves, Reis, and Ferramosca, 2009). Flandreau (1995Flandreau ( , 1996Flandreau ( , 2002Flandreau ( , 2004 extended the notion of gold points for the gold standard to bimetallic points for the bimetallic standard in the nineteenth century.…”
Section: Testing For Bullion Market Integrationmentioning
confidence: 99%
“…This was not the case in most other financial centres, where forward exchange markets developed in the aftermath of the First World War 3 . But this does not mean that foreign exchange intervention techniques were unknown elsewhere: recent historical research has shown that the central banks of peripheral countries like Portugal (Reis 2007;Esteves et al 2009), Norway (Øksendal 2008), or Sweden (Ögren 2007) were important players on the spot exchange market. Nowhere, however, the scale and scope of foreign exchange policy were comparable to those reached by the NBB in its early years.…”
Section: 1: Monetary Independence Under Fixed Exchange Ratesmentioning
confidence: 99%